Exosomes derived from miR-146a-overexpressing fibroblast-like synoviocytes in cartilage degradation and macrophage M1 polarization: a novel protective agent for osteoarthritis? - Wang, Huan; Zhang, Yue; Zhang, Chengfei; Zhao, Yan; Shu, Jun; Tang, Xuezhang (Frontiers in Immunology, 2024)
Introduction Pathological changes in the articular cartilage (AC) and synovium are major manifestations of osteoarthritis (OA) and are strongly associated with pain and functional limitations. Exosome-derived microRNAs (miRNAs) are crucial regulatory factors in intercellular communication and can influence the progression of OA by participating in the degradation of chondrocytes and the phenotypic transformation in the polarization of synovial macrophages. However, the specific relationships and pathways of action of exosomal miRNAs in the pathological progression of OA in both cartilage and synovium remain unclear. Methods This study evaluates the effects of fibroblast-like synoviocyte (FLS)-derived exosomes (FLS-Exos), influenced by miR-146a, on AC degradation and synovial macrophage polarization. We investigated the targeted relationship between miR-146a and TRAF6, both in vivo and in vitro, along with the involvement of the NF-κB signaling pathway. Results The expression of miR-146a in the synovial exosomes of OA rats was significantly higher than in healthy rats. In vitro, the upregulation of miR-146a reduced chondrocyte apoptosis, whereas its downregulation had the opposite effect. In vivo, exosomes derived from miR-146a-overexpressing FLSs (miR-146a-FLS-Exos) reduced AC injury and chondrocyte apoptosis in OA. Furthermore, synovial proliferation was reduced, and the polarization of synovial macrophages shifted from M1 to M2. Mechanistically, the expression of TRAF6 was inhibited by targeting miR-146a, thereby modulating the Toll-like receptor 4/TRAF6/NF-κB pathway in the innate immune response. Discussion These findings suggest that miR-146a, mediated through FLS-Exos, may alleviate OA progression by modulating cartilage degradation and macrophage polarization, implicating the NF-κB pathway in the innate immune response. These insights highlight the therapeutic potential of miR-146a as a protective agent in OA, underscoring the importance of exosomal miRNAs in the pathogenesis and potential treatment of the disease.